2010
DOI: 10.7205/milmed-d-10-00193
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Is the Most Commonly Reported Symptom and Predicts Other Symptoms of Post-Traumatic Stress Disorder in U.S. Service Members Returning From Military Deployments

Abstract: This study retrospectively reviewed records from current members of the U.S. military who had completed the PTSD Checklist (PCL) at 0 and 3-months after returning from deployments. Insomnia was the most commonly reported symptom of PTSD on the PCL and had the highest average severity scores. At initial screen, 41% of those who had been to Iraq or Afghanistan reported sleep problems. Those who had initially reported any insomnia had significantly higher overall scores for PTSD severity at follow-up than did ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
129
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 0 publications
6
129
1
Order By: Relevance
“…5,[10][11][12] Although there is a large body of work outlining disturbed sleep and insomnia in veterans, our study contributes uniquely in that it used a three-group design to investigate an issue that has been unclear: Does PTSD, TE, and/or simply being a veteran drive sleep disturbance, particularly in OEF/OIF/OND veterans? Given that disturbed sleep is part of the diagnostic criteria for PTSD 9 and that to our knowledge, most studies of sleep and PTSD have not examined this (the majority have used the PTSD Checklist to obtain PTSD symptom scores but do not specifically assess traumatic event exposure 5,8,11 ), it remains an important question to answer and one that we were specifically suited to examine within our sample. Results from our ANCOVAs indicated that the PTSD group differed from both control and TE groups on global sleep disturbances, as well as all PSQI subscales except efficiency and duration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,[10][11][12] Although there is a large body of work outlining disturbed sleep and insomnia in veterans, our study contributes uniquely in that it used a three-group design to investigate an issue that has been unclear: Does PTSD, TE, and/or simply being a veteran drive sleep disturbance, particularly in OEF/OIF/OND veterans? Given that disturbed sleep is part of the diagnostic criteria for PTSD 9 and that to our knowledge, most studies of sleep and PTSD have not examined this (the majority have used the PTSD Checklist to obtain PTSD symptom scores but do not specifically assess traumatic event exposure 5,8,11 ), it remains an important question to answer and one that we were specifically suited to examine within our sample. Results from our ANCOVAs indicated that the PTSD group differed from both control and TE groups on global sleep disturbances, as well as all PSQI subscales except efficiency and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing maladaptive coping strategies in veterans, such as using drugs and alcohol to cope, may be a way to improve disturbed sleep, 41 as current clinical screening protocols mostly focus on detecting substance use disorders. It is important to identify and address risk factors for worse sleep in veterans, given evidence that in addition to being a commonly reported symptom, 8 sleep has been shown to predict future psychopathology. 14,15 Thus, targeting sleep in veterans can improve current symptomatology (for those who have it), in addition to helping prevent the development of future psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with previous studies that have shown that sleep disturbances are highly prevalent and strongly correlated with PTSD in combat deployment military veterans. [42][43][44][45][46][47][48][49][50][51] Although sleep difficulties often follow TBI or blast exposure, 52 the present study suggests that prior blast exposure or TBI alone, in the absence of current chronic concussive symptoms, does not adversely affect sleep quality, insomnia, disruptive sleep disturbances, or objective sleep measures beyond the effects of PTSD. Indeed, post hoc analyses revealed that service members and veterans with PTSD endorsed higher scores on the ISI, PSQI, and PSQIA than those without PTSD diagnosis, regardless of presence or absence of blast exposure.…”
Section: Discussionmentioning
confidence: 99%